Near Real-Time Astrometry for Spacecraft Navigation with the VLBA: A Demonstration with the Mars Reconnaissance Orbiter and Odyssey. (4th January 2016) - Max-Moerbeck, W.; Brisken, W. F.; Romney, J. D.
Abstract: We present a demonstration of near real-time spacecraft astrometry with the VLBA. We detect the X-band downlink signal from Mars Reconnaissance Orbiter and Odyssey with the VLBA and transmit the data over the internet for correlation at the VLBA correlator in near real-time. Quasars near Mars in the plane of the sky are used as position references. In the demonstration we were able to obtain initial position measurements within about 15 minutes of the start of the observation. The measured positions differ from the projected ephemerides by a few milliarcseconds, and the repeatability of the measurement is better than 0.3 mas as determined from measurements from multiple scans. We demonstrate that robust and repeatable offsets are obtained even when removing half of the antennas. These observations demonstrate the feasibility of astrometry with the VLBA with a low latency and submilliarcsecond repeatability.